Formación universitaria intercultural para indígenas mayas de Yucatán, México - Rosado-May, Francisco Javier (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
This work presents important decisions made during the implementationof the intercultural educational model at the UniversidadIntercultural Maya de Quintana Roo, Mexico, in a context of povertyand conditions of lagging behind the rest of the society of theindigenous Yucatec Maya population. Within the legal frameworkof public universities in Mexico, the financing of projects, thedeveloping of intercultural pedagogy and designing the institutionalsettings, rested on elements that included learning/transmission andconstruction/innovation of knowledge that combined aspects of thelocal culture with conventional education. High figures on indicatorssuch as retention, graduation rate, employability, and quality ofthe academic programs, along with opinions from alumni, achievedduring the period of February 2007 to February 2015, indicate thatthe decisions and actions taken in the beginning of the constructionof the intercultural model at UIMQRoo, were in the right direction.

Mediante una descripción vivencial de la construcción de la Universidad Intercultural Maya de Quintana Roo, este trabajo presenta importantes decisiones tomadas y caminos andados para la implementación de un modelo educativo, intercultural, en un contexto de alto rezago y pobreza de los indígenas mayas en Quintana Roo. Sin descuidar las normas y políticas que aplican a instituciones públicas en México, los esquemas de financiamiento, arreglo institucional y pedagogía intercultural, desarrollados en la UIMQRoo, tomaron en cuenta elementos de aprendizaje/transmisión y de construcción/ innovación de conocimiento que combinan aspectos de la cultura local con la educación convencional. Altos indicadores de retención, titulación, empleabilidad y calidad de los programas educativos, así como opiniones de egresados, alcanzados de febrero 2007 a febrero 2015, hacen pensar que las decisiones condujeron hacia la dirección correcta.
Intercultural higher education for indigenous Yucatec Maya in Mexico
Keywords: Educación intercultural; Indígenas mayas; Educación indígena; Pedagogía intercultural; https://purl.org/pe-repo/ocde/ford#5.04.03